Influence of surface conductive tip on the area of contact between him and welding wire - Завгородній, В.В.; Абрамов, О.О.; Вичавка, А.А. (Problems of Tribology, 2016)
To ensure continuity of welding works must have a reliable contact between the tip and wire. The magnitude of the contact area depends on many factors. But one of the most important is the state of the surface of the inner channel tip. When performing welding using strumopidvidni tip that vyhovleni of different materials, in different ways, with different surface state, yii shorskistyu. During operation, the surface state of internal channel tip pereterpaye changes. When traffic on the wire feed tip as a consequence of friction and the passage of electric current, and action mikroiskor, a change in the contact area between the wire tip and that affects the value of the welding current and, consequently, the stability of the arc. Considered pattern changes in the area of contact between the conductive tip and welding wire depending on the state of the internal surface of the tip of the channel, its roughness. The identified location largest demolition tip. Naiden dependence of the contact area on the change of roughness. Detected roughness value at which the contact area is the maximum value. Optimalnyy defined surface state of internal channel tip.